Discrimination of Malaysian stingless bee honey from different entomological origins based on physicochemical properties and volatile compound profiles using chemometrics and machine learning - Sharin, Siti Nurhidayah; Sani, Muhamad Shirwan Abdullah; Jaafar, Mohd Azwan; Yuswan, Mohd Hafis; Kassim, Nur Kartinee; Manaf, Yanty Noorzianna; Wasoh, Helmi; Zaki, Nor Nadiha Mohd; Hashim, Amalia Mohd (Food chemistry, 2021)
•VOC markers can be used to differentiate honey from different stingless bee.•Honey chemical profiles are consistent with phylogenetic clustering.•Physicochemical and VOC profiles of stingless bee honey aid in honey authentication. Identification of honey origin based on specific chemical markers is important for honey authentication. This study is aimed to differentiate Malaysian stingless bee honey from different entomological origins (Heterotrigona bakeri, Geniotrigona thoracica and Tetrigona binghami) based on physicochemical properties (pH, moisture content, ash, total soluble solid and electrical conductivity) and volatile compound profiles. The discrimination pattern of 75 honey samples was observed using Principal Component Analysis (PCA), Hierarchical Clustering Analysis (HCA), Partial Least Square-Discriminant Analysis (PLS-DA), and Support Vector Machine (SVM). The profiles of H. bakeri and G. thoracica honey were close to each other, but clearly separated from T. binghami honey, consistent with their phylogenetic relationship. T. binghami honey is marked by significantly higher electrical conductivity, moisture and ash content, and high abundance of 2,6,6-trimethyl-1-cyclohexene-1-carboxaldehyde, 2,6,6-trimethyl-1-cyclohexene-1-acetaldehyde and ethyl 2-(5-methyl-5-vinyltetrahydrofuran-2-yl)propan-2-yl carbonate. Copaene was proposed as chemical marker for G. thoracica honey. The potential of different parameters that aid in honey authentication was highlighted.